2016
DOI: 10.1039/c6ra21025b
|View full text |Cite
|
Sign up to set email alerts
|

First-principle study for influence of an external electric field on the electronic structure and optical properties of TiO2

Abstract: The influence of external electric fields on the electronic structure and optical properties of TiO2 was studied using first-principle calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The max ionic force, max ionic displacement, and max stress component tolerance were 8.0 9 10 À2 eV A À1 , 2.0 9 10 À3 A, and 0.1 GPa, respectively. It was similar with the method reported by Zhao et al [52] Material Preparation: Synthesis of H 2 Ti 5 O 11 Á3H 2 O Yolk-shell spheres. In a typical procedure, diethylenetriamine (DETA, Sigma-Aldrich, 0.05 mL) was added dropwise to isopropyl alcohol (IPA, Sigma-Aldrich, 50 mL) with vigorously stirring.…”
Section: Experimental and Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…The max ionic force, max ionic displacement, and max stress component tolerance were 8.0 9 10 À2 eV A À1 , 2.0 9 10 À3 A, and 0.1 GPa, respectively. It was similar with the method reported by Zhao et al [52] Material Preparation: Synthesis of H 2 Ti 5 O 11 Á3H 2 O Yolk-shell spheres. In a typical procedure, diethylenetriamine (DETA, Sigma-Aldrich, 0.05 mL) was added dropwise to isopropyl alcohol (IPA, Sigma-Aldrich, 50 mL) with vigorously stirring.…”
Section: Experimental and Methodssupporting
confidence: 85%
“…[49,50] The generalized gradient approximation functional developed by Perdew and Wang (PW91) [51] was chosen as the correlation function, and DFT + U method with a value of Ti was set as 7.0 eV (U) based on the Ref. [52] For geometric optimization calculations, a plane-wave basis with a kinetic energy cutoff of was set as 340 eV. The k-points were sampled on Monkhorst-Pack grid of 2 9 2 9 1 for the unit cell or super cell.…”
Section: Experimental and Methodsmentioning
confidence: 99%
“…The improvement in conductivity of doped perovskite may be ascribed to the alteration of bandgap energy. 41 Moreover, the undoped CsPbBr 3 and doped CsPb 0.998 Sn 0.002 Br 3 perovskites dielectric functions are revealed in Fig. 4(f and g) .…”
Section: Resultsmentioning
confidence: 88%
“…The lattice distortion caused by the mutation of lattice parameters may lead to change in the microscopic electric structure, band structure, and density of states, similar to the results reported in ref. 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Zhao et al . 17 reported the influence of external electric fields on the electronic structure and optical properties of TiO 2 . They found that the band gap of TiO 2 becomes narrower with increasing electric field strength, decreasing to 0 eV when the electric field is 0.25 eV.…”
Section: Introductionmentioning
confidence: 99%